2013
DOI: 10.2298/vsp1304368j
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin and iron metabolism disorders in patients with chronic kidney disease

Abstract: Hepcidin may serve as a marker for better diagnosing and monitoring anemia and iron metabolism disorders in CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Hepcidin inhibits iron egress out of cells through binding and inducing degradation of its receptor ferroportin. Ferroportin, the only known mammalian iron exporter is mainly expressed in epithelial cells in duodenum and macrophages (Jelic et al, 2013;Pinnix et al, 2010). Suppression of hepcidin expression or hepcidin deficiency would cause enhanced iron egress out of macrophages, leading to iron overload in various organs, associated with neoplasia, arthropathy and neurodegenerative diseases (Jelic et al, 2013;Pinnix et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hepcidin inhibits iron egress out of cells through binding and inducing degradation of its receptor ferroportin. Ferroportin, the only known mammalian iron exporter is mainly expressed in epithelial cells in duodenum and macrophages (Jelic et al, 2013;Pinnix et al, 2010). Suppression of hepcidin expression or hepcidin deficiency would cause enhanced iron egress out of macrophages, leading to iron overload in various organs, associated with neoplasia, arthropathy and neurodegenerative diseases (Jelic et al, 2013;Pinnix et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is began with DM nephropathy that if continued and uncontrolled will cause chronic kidney failure. 9 Blood Urea Nitogen (BUN) and creatinine levels pre-HD were found to be 49.49±15.6 mg/dL and 10.77±2.7 mg/dL, respectively. The mean of creatinine level in this study was higher than a previous study by Krishnamurthy 7 which showed a creatinine level of 7.22±2.22 mg/dL.…”
Section: Sexmentioning
confidence: 99%
“…This number was lower compared with the results of a study conducted by Jeli in Serbia (88%). 9 Hypertension is one of risk factor for chronic renal disease, this maybe because a severe and uncontrolled hypertension will cause changes in arterioles vessel walls (arteriol fibrinoid sclerosis) and will impair the renal function, on the other side, hypertension may also be an impact from chronic renal disease (renal hypertension). 9 There was a total of 28.9% of subjects who had risk factor for diabetes mellitus.…”
Section: Sexmentioning
confidence: 99%
“…Liver is the central organ governing systemic iron homeostasis, where hepcidin is primarily secreted by hepatocytes and regulates iron flux by interacting with its receptor ferroportin, which is associated with the internalization and degradation of ferroportin, thereby reducing iron egress from macrophages and iron absorption from the small intestine (14)(15)(16). Iron, an essential element, is important for a variety of biological processes (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic iron homeostasis is deliberately modulated by the hepcidin-ferroportin regulatory axis (14,(19)(20)(21). Ferroportin is the only known mammalian iron exporter, mainly expressed in epithelial cells in duodenum and macrophages, and is critical for controlling iron egress (15,16). Through the hepcidin-ferroportin axis, downregulated hepatic hepcidin increases the serum iron level by promoting iron absorption from enterocytes in duodenum and iron release from macrophages (22).…”
Section: Introductionmentioning
confidence: 99%